Can 595-nm Pulsed Dye Laser in Conjunction With an Optical Clearing Agent Improve the Treatment of Port-Wine Stains?. Issue 5 (11th May 2022) - Yu, Wenxin; Chen, Yanyu; Cen, Qingqing; Zhu, Jiafang; Lin, Xiaoxi
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Studies have demonstrated that glycerol can act as an optical clearing agent (OCA) to increase the light penetration through the skin and laser deposition to the target chromophore, thus potentially increasing the efficacy of laser treatment. OBJECTIVE: To evaluate whether a pulsed dye laser (PDL) in combination with an OCA can increase the efﬁcacy in treating port-wine stains (PWSs). METHODS: Thirteen patients with untreated PWSs underwent 3 treatment sessions at 6-week intervals. Each PWS was divided into OCA + PDL sites (PDL treatment after topical use of 0.5 mL hydrous glycerol for 5 minutes), PDL sites, and untreated sites. The chromametric evaluation and visual evaluation (VAS) of the efﬁcacy and the assessment of side effects were conducted 3 months after the ﬁnal treatment. RESULTS: Visual evaluation was 2.69 versus 2.07 ( p = .025) and 3.38 versus 3.07 ( p = .04) for OCA + PDL and PDL-only sites after the first and second sessions. After the third session, the chromameter and VAS indicated no significant difference between the 2 sites. Permanent side effects were not observed. CONCLUSION: Greater efficacy was observed after the first 2 treatments on the OCA + PDL sites. Although after multiple sessions, the OCA + PDL treatment did not improve efficacy over just PDL alone.